PENINGKATAN AKTIVITAS BELAJAR PESERTA DIDIK MELALUI PENGGUNAAN METODE SQ3R PADA PEMBELAJARAN PAI KELAS V SDN 13 AIA MANYURUAK - Mariyono, Mariyono (CV Sintesia, 2025)
Research on the SQ3R method has been carried out by Peter C. Ruenitz in a journal entitled Discussion-Based Instruction in Drug Metabolism. Accordingly, in a journal entitled A First Year Experience Orientation Course for Engineer by Dr. Eric P. Soulsby. In these two journals, the SQ3R method was used to study textbooks, after students understood the textbooks, discussions were held. In the discussion, students provide responses in both written and oral form. Based on the analysis of the research results, it was found that the learning activities of students with the SQ3R method experienced an increase in PAI learning on the subject of knowing Allah's Apostle. It means that it can be concluded that the SQ3R method has an effect on student learning activities in PAI Class V learning because it can improve student learning outcomes. To increase students' learning activities, teachers can use the SQ3R method as an alternative method that can increase interest in learning. Students read teaching materials in a directed manner and have optimal thinking skills. In reading teaching materials, students are trained to make questions, answer questions, seek answers and conclude learning. This makes learning more meaningful and supports the concept of independent learning for students, where learning involves students actively in learning.